Optimalisasi Pencegahan Triple Burden pada Ibu Hamil Berbasis Flipbook Gizi 1.000 Hari Pertama Kehidupan di Desa Bangun Rejo - Mesrida Simarmata; Srininta Srininta; Ariska Fauzianty; Rolasnih Lilista Simbolon; Kamelia Sinaga; Rasmi Manullang; Eka Purnamasari; Yuliska Febriyan; Misno Misno (CV. ALIM'SPUBLISHING, 2026)
Indonesia faces a triple burden of malnutrition, including anemia, chronic energy deficiency, and obesity among women. In 2024, anemia prevalence reached 30.7%, while SDG 2025 data reported that 28% of women experienced malnutrition. This study aimed to improve pregnant women’s knowledge of triple burden prevention through the